Analysis of English Lesson Plans of Junior High School Teachers in Bumiayu District - Bunga Putri Maulia; Khairunnisa Dwinalida (Jurnal Indonesia Sosial Teknologi, 2024)
This study aims to find out the quality of lesson plans created by English teachers of Junior High Schools at Bumiayu Brebes Regency. The type of study is quantitative descriptive with documentation techniques. The instrument assessment in this study used an assessment sheet made with the 2013 curriculum standard by referring to Circular Letter Number 14 of 2019 concerning the Simplification of Lesson Plans, which the expert has validated. The results of this study is that the English lesson plans generally dominated in the “Below Average” category with 79%. It follows the results, which shows that the “Very Good” category is 0%, the “Good” category is 2.6%, the “Average” category is 18.4%, and the “Below Average” category is 79%. The data results are stated based on the facts according to the field, and there is no training or counselling on the preparation of good and correct lesson plans that government regulations have determined according to the 2013 curriculum. It needs to be the main focus that the competence of Junior High School English teachers at Bumiayu Brebes Regency has not fully mastered the writing of lesson plans according to the standard of writing lesson plans